Stability in community-acquired pneumonia: one step forward with markers?. Issue 11 (16th September 2009) - Menéndez, R; Martinez, R; Reyes, S; Mensa, J; Polverino, E; Filella, X; Esquinas, C; Martinez, A; Ramirez, P; Torres, A
Abstract : Background: Biological markers as an expression of systemic inflammation have been recognised as useful for evaluating the host response in community-acquired pneumonia (CAP). The objective of this study was to evaluate whether the biological markers procalcitonin (PCT) and C-reactive protein (CRP) might reflect stability after 72 h of treatment and the absence of subsequent severe complications. Methods: A prospective cohort study was performed in 394 hospitalised patients with CAP. Clinical stability was evaluated using modified Halm's criteria: temperature ⩽37.2°C; heart rate ⩽100 beats/min; respiratory rate ⩽24 breaths/min; systolic blood pressure ⩾90 mm Hg; oxygen saturation ⩾90%; or arterial oxygen tension ⩾60 mm Hg. PCT and CRP levels were measured on day 1 and after 72 h. Severe complications were defined as mechanical ventilation, shock and/or intensive care unit (ICU) admission, or death after 72 h of treatment. Results: 220 patients achieved clinical stability at 72 h and had significantly lower levels of CRP (4.2 vs 7 mg/dl) and of PCT (0.33 vs 0.48 ng/ml). Regression logistic analyses were performed to calculate several areas under the ROC curve (AUC) to predict severe complications. The AUC for clinical stability was 0.77, 0.84 when CRP was added (p = 0.059) and 0.77 when PCT was added (p = 0.45). When clinical stability was achieved within 72 h and marker levels were below the cut-off points (0.25 ng/ml for PCT and 3 mg/dl for CRP), no severe complications occurred. Conclusions: Low levels of CRP and PCT at 72 h in addition to clinical criteria might improve the prediction of absence of severe complications.